Computing Performance Optimization Through Parallelization: Techniques and Evaluation - Akintayo, Taiwo Abdulahi; Olobo, Neibo Augustine; Atinuke, Aregbesola Taobat; AbdulKareem, Idayat Olaide (Darul Yasin Al Sys, 2024)
Parallelization has become a cornerstone technique for optimizing computing performance, especially in addressing the growing complexity and scale of modern computational tasks. By leveraging concurrent processing capabilities of multi-core processors, GPUs, and distributed systems, parallel computing enables the efficient execution of large-scale problems that would otherwise be computationally prohibitive. This paper explores various parallelization techniques, including data parallelism, task parallelism, pipeline parallelism, and the use of GPUs for massive parallel computations. We also examine the key performance evaluation metrics such as speedup, efficiency, Amdahl’s Law, scalability, and load balancing that are critical in assessing the effectiveness of parallelization strategies. Through case studies in scientific simulations, machine learning, and big data analytics, we demonstrate how these techniques can be applied to real-world problems, offering significant improvements in execution time and resource utilization. The paper concludes by discussing the trade-offs involved in parallel computing and suggesting future avenues for optimizing parallelization methods in the context of evolving hardware and software technologies.